2016
DOI: 10.1007/s00405-016-4133-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of chlorophyll c2 for seasonal allergic rhinitis: single-center double-blind randomized control trial

Abstract: Chlorophyll c2 extracted from Sargassum horneri improved allergic symptoms in an animal model of allergic rhinitis. In the present study, we explored the efficacy of chlorophyll c2 in patients with seasonal allergic rhinitis. This was a single-center, randomized, double-blind placebo-controlled trial. Sixty-six patients aged 20-43 years, each with a 2-year history of seasonal allergic rhinitis, were randomly assigned to receive either a single daily dose (0.7 mg) of chlorophyll c2 or placebo for 12 weeks. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Chl b and Chl c are also important chlorophylls found in seaweeds. They are accessory pigments in the antenna system of Chl a [62,63,64,65]. The present study revealed that the variation of these three kinds of chlorophylls was mainly affected by phylum, namely, Ochrophyta, Chlorophyta, and Rhodophyta, but not by sampling location (Table 2).…”
Section: Discussionmentioning
confidence: 60%
“…Chl b and Chl c are also important chlorophylls found in seaweeds. They are accessory pigments in the antenna system of Chl a [62,63,64,65]. The present study revealed that the variation of these three kinds of chlorophylls was mainly affected by phylum, namely, Ochrophyta, Chlorophyta, and Rhodophyta, but not by sampling location (Table 2).…”
Section: Discussionmentioning
confidence: 60%
“…Furthermore, chlorophyll C2 inhibited IgE-mediated allergic responses in rhinitis mouse model 36 and decreased the rescue medication scores in clinical double-blind trial of seasonal allergic rhinitis. 37 Therefore, we suggest that SD including various types of chlorophyll shows potential as an anti-allergic agent for treatment of allergic disorders like food allergies.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the increased concentration of anti-inflammatory cytokines IL-10 found in the WGJ intervention group can be elucidated by the high content of chlorophyll, flavonoids, and superoxide dismutase in wheatgrass [47]. Chlorophyll, which constitutes one of the major components of wheatgrass, may contribute to the treatment of various inflammation-related diseases, such as dengue [48], cholangiocarcinoma [49], allergic rhinitis [50], and acne vulgaris [51].…”
Section: Discussionmentioning
confidence: 99%